2013
DOI: 10.1371/journal.pone.0061634
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-AMP Mediated Regulation of ABCB mRNA Expression in Mussel Haemocytes

Abstract: BackgroundThe multixenobiotic resistance system (MXR) allows aquatic organisms to cope with their habitat despite high pollution levels by over-expressing membrane and intracellular transporters, including the P-glycoprotein (Pgp). In mammals transcription of the ABCB1 gene encoding Pgp is under cAMP/PKA-mediated regulation; whether this is true in mollusks is not fully clarified.Methodology/Principal FindingscAMP/PKA regulation and ABCB mRNA expression were assessed in haemocytes from Mediterranean mussels (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 63 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…As expected, in mussels caged at the petrochemical site of Priolo AChE immunopositivity was reduced, and limited almost solely to hemocytes. In marine mussels, hemocytes possess a complex cell signaling network with high homology with that of vertebrates, that allows them to modulate their own functions (Humphries and Yoshino, 2003;Franzellitti and Fabbri, 2013). However, little it is known on the physiological roles of these signaling pathways in mussel hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, in mussels caged at the petrochemical site of Priolo AChE immunopositivity was reduced, and limited almost solely to hemocytes. In marine mussels, hemocytes possess a complex cell signaling network with high homology with that of vertebrates, that allows them to modulate their own functions (Humphries and Yoshino, 2003;Franzellitti and Fabbri, 2013). However, little it is known on the physiological roles of these signaling pathways in mussel hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We measured urinary angiotensinogen (AGT) using an ELISA (Rat Total Angiotensinogen Assay Kit, Clontech Laboratories) according to the manufacturer's instructions and plasma AGT via immunoblotting. Urinary cAMP was measured by using an ELISA kit (DetectXTM direct cAMP enzyme immunoassay kit, Arbor Assays) according to the manufacturer's instructions (21).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the increases in cAMP levels and PKA activities in the mantle/gonads of propranolol‐exposed mussels observed in same study support an indirect stimulation of propranolol by acting as a 5‐HT1 receptor antagonist. It is worth noting that transcripts encoding 5‐HT1 receptors have been detected in several mussel tissues, including mantle/gonads . Furthermore, Garnerot et al showed that serotoninergic fibers are apparently absent or scarce in bivalve digestive gland, whereas a high concentration of these fibers is detected in gonads.…”
Section: Pharmaceutical Interactions With Marine Faunamentioning
confidence: 99%
“…As recently reviewed , the cAMP‐dependent pathway is well known for regulating several functions in mollusks and, among others, the nucleotide modulates the availability of mantle glycogen as fuel for gonad maturation. Furthermore, recent investigations have suggested a role of cAMP in the control of key cytoprotective mechanisms providing an adaptive advantage for marine bivalves to cope with environmental challenges . Therefore, conservation of therapeutic effects of pharmaceuticals targeting cell‐signaling mediators may impair the ability of organisms to cope with environmental stressors, thus potentially undermining their fitness.…”
Section: Pharmaceutical Interactions With Marine Faunamentioning
confidence: 99%